Formação didático-pedagógica em programas de pós-graduação em enfermagem da região norte do Brasil - SILVEIRA, Stelacelly Coelho Toscano (Universidade Federal do Pará, 2023)
Study analyzed the Action and Pedagogical Reasoning of permanent teachers for the pedagogical didactic formation in stricto sensu Nursing postgraduate programs of the Northern region of Brazil. METHOD: Mixed Methods Research. This research included permanent PGGENF teachers in the Northern region, listed on the Sucupira Platform as a permanent teacher in PPGENF in the Northern region, who taught discipline in one of the areas of concentration in 2018. For data collection, oral and documentary sources were used. Lattes curriculum, Sucupira Platform and interviews. The process took place in three stages, consisting of (1) Characterization of teachers, (2) Analysis of the structure of the Pedagogical Political Project (PPP) and (3) Semistructured Interview, interconnected with each other and with the proposed study object, indicating to find the relations of action and pedagogical action of teachers of postgraduate programs in the Northern region. Data analysis occurred in two moments through qualitative approaches through the Constant Comparison Method proposed by Strauss and Corbin (2008) and quantitative through the descriptive statistical technique. The guidelines and norms for research with human beings established in Resolution 466/2012 of the National Health Council were obeyed. RESULTS AND DISCUSSION: Initially 23 codes aligned with Shulman's proposal emerged. This grouping occurred due to the magnitude and significance of the data considering the interview and PPP of the programs. For the organization of the results, two goalscategories were established: “General pedagogical knowledge, Knowledge of the educational context and Students knowledge and its characteristics shaping the understanding of the pedagogical didactic formation” and “The academic formation and the Wisdom acquired with the teaching practice as reinforcers of an Action and Pedagogical Reasoning ”. CONCLUSION: Among the Pedagogical Action and Reasoning Model (APRM), the most expressive observation was the phases of comprehension and transformation, respectively, shown more objectively in the teaching phase. This movement allowed us to understand a cycle of reflections to new ways of learning, even if incipiently. It is important to highlight the contribution of the program, and how much the APRM can contribute to help explain the development of teacher education of future trainers within the field of nursing knowledge, contributing to further education, starting from the resignification of those who teach.